Patient participant, healthcare professional, and stakeholder perspectives on the Pharmacy Homeless Outreach Engagement Non-medical Independent prescribing Rx (PHOENIx) community pharmacy pilot randomised controlled trial. - Hannah Scobie; Shona MacKinnon; Karen Wood; Alessio Albanese; Yvonne Cunningham; Andrea Williamson; Jane Moir; Andrew McPherson; Cian Lombard; Steven Ross; Adnan Araf; Helena Heath; et al. (PLoS ONE, 2025)
Background People experiencing homelessness (PEH) face complex health and social care needs, contributing to poor health outcomes and premature mortality. The Pharmacy Homeless Outreach Engagement Non-medical Independent prescribing Rx (PHOENIx) intervention was developed to address these challenges through assertive outreach by NHS pharmacist independent prescribers working with third sector homelessness charity workers for PEH presenting to community pharmacy. This qualitative study aims to explore participant, healthcare professional, and stakeholder perceptions of the PHOENIx intervention and acceptability of trial procedures. Methods Semi-structured interviews were conducted with trial participants, internal stakeholders (healthcare professionals/researchers), and external stakeholders (national and local) across two intervention sites (Glasgow and Birmingham) between March 2023 and February 2024. Data was analysed thematically using Normalisation Process Theory (NPT) as a conceptual framework. Results Participants (n = 26; usual care n = 7; intervention n = 19) viewed PHOENIx as distinctively comprehensive, consistent, and caring, valuing its holistic approach and the trusting relationships developed with the team. Stakeholders (n = 16; internal n = 5; external n = 11) recognised PHOENIx's potential to fill gaps in current service provision for PEH, appreciating its flexible, outreach-based model. Challenges identified included resource constraints, integration with existing services, and concerns about long-term sustainability. Conclusions The PHOENIx intervention shows promise in providing accessible, comprehensive healthcare which was acceptable to PEH. Its success in engaging this underserved population offers valuable lessons for service development. However, addressing challenges around resources, scalability, and sustainability will be important considerations for a future trial and wider implementation and expansion.